2014
DOI: 10.1038/cddis.2014.45
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidogenic variant of apolipoprotein A-I elicits cellular stress by attenuating the protective activity of angiogenin

Abstract: Amyloidogenic ‘gain-of-function' mutations in apolipoprotein A-I (ApoA-I) gene (APOA1) result in systemic amyloidosis characterized by aggregate deposition and eventually cell death. However, how amyloidogenic variants of ApoA-I induce cell death is unknown. Here we report that one of the mechanisms by which amyloidogenic ApoA-I induces cell death is through attenuating anti-stress activity of angiogenin (ANG), a homeostatic protein having both pro-growth and pro-survival functions. Under growth conditions, AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…We previously demonstrated that L75P-ApoA-I transfectants are more sensitive than control cells to serum withdrawal and hypothesized that cell death occurred via apoptosis [ 19 ]. To confirm this hypothesis, we analysed signs of apoptosis in HepG2 cells expressing the amyloidogenic variant L75P-ApoA-I.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously demonstrated that L75P-ApoA-I transfectants are more sensitive than control cells to serum withdrawal and hypothesized that cell death occurred via apoptosis [ 19 ]. To confirm this hypothesis, we analysed signs of apoptosis in HepG2 cells expressing the amyloidogenic variant L75P-ApoA-I.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that, in L75P-ApoA-I transfectants, the amyloidogenic variant is retained within the cell, representing a stress factor [ 19 ]. Thus, we indirectly analysed the redox status of L75P-ApoA-I expressing cells by immunoblotting analysis of serine/threonine kinase protein kinase B (best known as AKT), MAP kinase p38 (MAPK) and the stress-activated protein kinase/Jun-amino-terminal kinase (SAPK/JNK) ( Figure 1 D–I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In AApoAI patients, ApoAI and HDL plasma levels are generally lower than in normal subjects , although this seems not to be the cause of cardiovascular diseases . ApoAI‐decreased plasma levels may be related to the lower amount of secreted amyloidogenic variants with respect to wild‐type ApoAI, as demonstrated for L75P‐AApoAI overexpressed in stably transfected human hepatic cells , as well as for L75P‐ and L174S‐AApoAI variants in transiently transfected COS‐7 cells .…”
Section: Apoai and Amyloidogenicitymentioning
confidence: 98%
“…Haploinsufficiency of angiogenin, furthermore, is a risk factor of Alzheimer's disease. Amyloidogenic variant of apoA-I apparently induces cell death through reducing angiogenin expression to attenuate antistress activity [ 47 ]. These findings suggest that apoA-I not only has a role to regulate cholesterol homeostasis in the brain but also protects the brain from injury and stress.…”
Section: Production and Function Of Apoe And Apoa-i In The Brainmentioning
confidence: 99%